2015
DOI: 10.2166/wst.2015.265
|View full text |Cite
|
Sign up to set email alerts
|

Flotation of algae for water reuse and biomass production: role of zeta potential and surfactant to separate algal particles

Abstract: The effect of chemical coagulation and biological auto-flocculation relative to zeta potential was examined to compare flotation and sedimentation separation processes for algae harvesting. Experiments revealed that microalgae separation is related to auto-flocculation of Anabaena spp. and requires chemical coagulation for the whole period of microalgae cultivation. In addition, microalgae separation characteristics which are associated with surfactants demonstrated optimal microalgae cultivation time and sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…), as at low Σ (absolute value), the repulsion of the double layer is minimum and surfaces are able to be close enough to sense LVW and AB forces (Henderson et al . ; Kwak & Kim ). Henderson et al .…”
Section: Chemical and Physical–chemical Methodsmentioning
confidence: 97%
“…), as at low Σ (absolute value), the repulsion of the double layer is minimum and surfaces are able to be close enough to sense LVW and AB forces (Henderson et al . ; Kwak & Kim ). Henderson et al .…”
Section: Chemical and Physical–chemical Methodsmentioning
confidence: 97%
“…Furthermore, the harvesting efficiency of flotation process can be affected by the electric charge of the bubble. Kwak and Kim 29 found that bubbles constituted by either air or carbon dioxide carried the negative charge in pH range of 4 to 11. Therefore, the algae can connect bubbles with C 16 TAB by electric force.…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, this complex containing algae and C 16 TAB was more positive and hydrophobic outside. It was recognized that bubbles in the flotation are electronegative 29 and hydrophobic. Therefore, this complex could attach to the bubble easily, resulting in a higher flotation recovery.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of chemical coagulation and biological auto-flocculation relative to ζ-potential was studied to compare flotation and sedimentation separation processes for algae harvesting [14]. The experiments revealed that microalgae separation was related to auto-flocculation of Anabaena spp.…”
Section: Trends In Green Chemistrymentioning
confidence: 99%
“…The extracted ore was treated at first by gravimetry (during the period of and by differential flotation (during the period of [1950][1951][1952][1953][1954][1955][1956][1957][1958]. Physical, chemical, and mineralogical characterization (X-ray diffraction), reflected light microscopy, scanning electron microscope of these samples were performed.The effect of chemical coagulation and biological auto-flocculation relative to ζ-potential was studied to compare flotation and sedimentation separation processes for algae harvesting [14]. The experiments revealed that microalgae separation was related to auto-flocculation of Anabaena spp.…”
mentioning
confidence: 99%